Pengaruh Kepuasan Merek, Loyalitas Merek, Kelekatan Merek, dan Kecintaan Merek terhadap Kosmetik Wardah di Swalayan Luwes Kota Boyolali. - Khusna Ade Prasetyo; Donna Setiawati; Listyowati Puji Rahayu (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the influence of brand satisfaction and brand love on brand loyalty toward Wardah cosmetic products. The research employed a quantitative approach with an associative research design to examine the relationships among the variables. The population consisted of consumers who had used Wardah cosmetic products, while the sample was selected using a purposive sampling technique based on predetermined criteria. Primary data were collected through a structured questionnaire distributed to respondents and analyzed using multiple linear regression with the assistance of IBM SPSS Statistics. The findings reveal that brand satisfaction has a positive and significant effect on brand loyalty, indicating that consumers who are satisfied with Wardah products are more likely to remain loyal to the brand. Furthermore, brand love also has a positive and significant effect on brand loyalty, demonstrating that consumers’ emotional attachment to the brand strengthens their commitment and intention to repurchase. Simultaneously, brand satisfaction and brand love significantly influence brand loyalty. These findings suggest that maintaining high product quality, fulfilling consumer expectations, and fostering strong emotional relationships with customers are essential strategies for enhancing long-term customer loyalty toward Wardah cosmetic products.